Bundesweite Entwicklung der Grundwasserstände seit 1991: Langzeittrends, Variabilität und Auswirkungen der jüngsten Trockenphase - Maria Wetzel; Stefan Broda; Mariana Gomez; Markus Zaepke; Patrick Clos; Stefan Kunz; Tanja Liesch; Marc Ohmer; Bastian Habbel; Michel Wingering; Bernhard Pitschka; Antje Roucka; et al. (Grundwasser, 2026)
Zusammenfassung Die Studie untersucht die Entwicklung der Grundwasserstände in Deutschland anhand von 5844 Messstellen sowie deren Reaktionsdynamik gegenüber klimatologischen Antrieben im Referenzzeitraum 1991–2020. Zusätzlich wird die Entwicklung seit 2018 im Kontext der außergewöhnlichen Dürreperiode betrachtet, um die Reaktionsfähigkeit und Vulnerabilität der Grundwassersysteme gegenüber extremen klimatischen Bedingungen zu bewerten. Erstmals erfolgt diese Auswertung bundesweit einheitlich und in enger Zusammenarbeit mit den zuständigen Landesbehörden. An 43 % der untersuchten Messstellen werden signifikante Trends festgestellt, überwiegend in Form fallender Grundwasserstände mit einem Medianrückgang von 0,9 cm pro Jahr. Dies entspricht einem jährlichen Rückgang von 0,5 %, bezogen auf die Spannweite der jeweiligen Grundwasserganglinie. Diese Entwicklungen sind deutschlandweit erkennbar, jedoch regional unterschiedlich ausgeprägt und überwiegend klimatisch bedingt. Um Unterschiede in der Reaktionsdynamik systematisch zu erfassen, werden die Messstellen anhand ihrer Autokorrelationslängen in vier Dynamikklassen eingeteilt. Mit abnehmender Dynamik zeigt sich für den Referenzzeitraum eine Zunahme langfristiger Trends (von −0,3 % pro Jahr in Dynamikklasse 1 bis −1,16 % pro Jahr in Klasse 4) sowie eine höhere Persistenz klimatischer Effekte. Träge Systeme reagieren verzögert und sind damit nachhaltiger von Niedrigständen betroffen (Median: 9,8 Monate), während schnell reagierende Systeme kürzere Niedrigstandsphasen (Median: 2,2 Monate) aufweisen und sich rascher erholen. Besonders in der Entwicklung seit 2018 werden diese Unterschiede deutlich: Rund 60 % der trägen Messstellen weisen über fünf Jahre hinweg anhaltend niedrige Grundwasserstände auf, wobei etwa 20 % neue Niedrigstände erreichen und damit unterhalb der Minimalwerte der Referenzperiode liegen. Die Ergebnisse verdeutlichen den engen Zusammenhang zwischen klimatischer Variabilität und Grundwasserdynamik und bilden eine Grundlage für die fortlaufende Bewertung der Grundwasserstandsentwicklung in Deutschland.

Urban morphology and the heat island effect in African cities: Evidence from Ghana, Togo, and Tanzania - Stephan Schmidt; Yucheng Zhang; Wenzheng Li; Houpu Li (Remote Sensing Applications: Society and Environment, 2026)

The role of hydrogen sulfide and trisulfur radical ion in molybdenum transport by hydrothermal fluids: implications for porphyry-epithermal Cu-Au-Mo deposits - Maria A. Kokh; Gleb S. Pokrovski; Stephan Klemme; Christian Schmidt; Clément Laskar; Jean-Louis Hazemann; Denis Testemale; Isabelle Kieffer; Olivier Proux; Eric Lahera; Harald Müller; Elena F. Bazarkina; et al. (Geochimica et Cosmochimica Acta, 2026)

GC-MS analysis of essential sandalwood oils with in vitro activity against Madurella mycetomatis - Stephan Seegers; Shereen O. Abd Algaffar; Prabodh Satyal; William N. Setzer; Sami A. Khalid; Thomas J. Schmidt (Phytochemistry Letters, 2025)

Signatures of Polar Vortex Weakening in the MLTI: A Review - V. L. Harvey; D. Aggarwal; E. Becker; M. Bittner; B. Funke; L. Goncharenko; J. Jia; R. Lieberman; H.-L. Liu; V. Maliniemi; A. Marchaudon; H. Nesse; et al. (Surveys in Geophysics, 2025)
This paper is a collaborative effort that originated at the International Space Science Institute Workshop on “Physical links between Weather and Climate in Space and the Lower Atmosphere” held 22–26 January 2024. Many scientists attended that workshop and contributed their expertise related to polar vortex impacts on upper atmosphere variability. This paper summarizes well-known and newly reported signatures of polar vortex weakening on mesosphere–lower-thermosphere (MLT) temperature, winds, composition, planetary waves, gravity waves, tides, and ionospheric foF2. A variety of observational and modeling results are shown and are consistent with previously published variations in the dynamical and chemical state of the MLT and ionosphere during weak vortex events. We present Superposed Epoch Analysis (SEA) of upper atmosphere diagnostics and phenomena where day 0 is the onset of major SSWs. We also present SEAs where day 0 is the onset of stratopause warmings followed by elevated stratopause events. Our goal in performing two SEAs is to test the sensitivity of 10 hPa versus 1 hPa winds to predict upper atmosphere variability. Results suggest that zonal winds and the semidiurnal migrating solar tide (SW2) in the MLT are more sensitive to zonal wind reversals at 1 hPa rather than 10 hPa. Alternatively, the non-migrating DW2 tide in the equatorial upper mesosphere is best predicted by planetary wave-1 amplitudes in the winter high-latitude upper stratosphere rather than zonal wind reversals. A notable aspect of both SEAs is extremely large event-to-event variability in all diagnostics. Thus, conclusions drawn based on any one event are less robust than those based on many events.

Occurrence and origin of thallium in mineral and thermal waters from the northern Upper Rhine Graben and adjacent regions, Germany - Senta Wittig; Rafael Schäffer; Thomas Kirnbauer; Matthias Bockstiegel; Nils Michelsen; Sven Philipp; Stefanie Schmidt; Stephan Weinbruch (Grundwasser, 2025)
Although thallium is a widespread and highly toxic element, it is rarely investigated in environmental chemistry due to its typically low concentrations in water. Consequently, little is known about the occurrence of thallium in groundwater and its origin. Here we show that high thallium concentrations of 5 up to 99 µg/l occur in Hesse exclusively in Na-Cl-waters and are locally clustered within the Taunus Border Zone. These variable concentrations seem to result from different thallium sources, varying mixing ratios of brine components, and varying degrees of thallium incorporation in hydrothermal minerals. We present evidence for a thallium origin from Zechstein (Permian) and Oligocene evaporites. A third possible source are basement brines from the Rhenish Massif. As the evaporite deposits are located tens of kilometers away from thallium-bearing wells, high thallium concentrations appear to be a good indicator of deep and regionally circulating brines.

New insights on the formation of the polymetamorphic Felbertal tungsten deposit (Austria, Eastern Alps) revealed by CL, EPMA, and LA-ICP-MS investigation - Cordula P. Haupt; Joachim Krause; Bernhard Schulz; Jens Götze; Johannes Chischi; Jasper Berndt; Stephan Klemme; Steffen Schmidt; Karsten Aupers; Nils Reinhardt (Mineralium Deposita, 2025)
The Felbertal tungsten deposit is the only economic scheelite mine in Europe, yet its genesis is not fully understood. It has been argued recently that the formation of the deposit is most likely related to granitic intrusions of Variscan age, contrasting a previously suggested syn-depositional stratabound origin of Early Cambrian age. Solving this controversy remains challenging due to the polymetamorphic evolution of the deposit, which experienced both Variscan and Alpine metamorphism. In this contribution we present a comprehensive new data set of scheelite major, minor, and trace element concentrations from multiple scheelite generations of the Felbertal deposit along with microstructural observations. Our results show that Mo, Mo/Mn, REE, Y/Ho, Nb, and Nb/Ta in scheelite are variable within the different scheelite generations and are predominantly controlled by the host-rock lithologies on the local scale, whereas in general the data show a strong response to the shift of P, T, and pH upon changing magmatic-hydrothermal to metamorphic conditions. For the first time, we identify remnants of primary scheelite in the Western Ore Zone. The presented data support a magmatic-hydrothermal origin of the first scheelite mineralization during the Variscan orogeny with primary scheelite being characterized by wing-shaped REE patterns with a negative Eu-anomaly, high trace element concentrations, non-chondritic Y/Ho, and high Nb/Ta. Primary scheelite underwent metamorphic/hydrothermal alteration (recrystallization and dissolution-reprecipitation processes) during the Variscan and Alpine orogeny. This case study highlights that indicative mineralization-controlling geochemical ratios like Sr/Mn cannot be applied for polymetamorphic tungsten deposits like Felbertal.

Phylogenomics and biogeography of sawflies and woodwasps (Hymenoptera, Symphyta) - Saskia Wutke; Stephan M. Blank; Jean-Luc Boevé; Brant C. Faircloth; Frank Koch; Catherine R. Linnen; Tobias Malm; Gengyun Niu; Marko Prous; Nathan M. Schiff; Stefan Schmidt; Andreas Taeger; et al. (Molecular Phylogenetics and Evolution, 2024)

No general support for functional diversity enhancing resilience across terrestrial plant communities - Lucrecia Lipoma; Stephan Kambach; Sandra Díaz; Francesco María Sabatini; Gabriella Damasceno; Jens Kattge; Christian Wirth; Scott R. Abella; Carl Beierkuhnlein; Travis R. Belote; Markus Bernhardt‐Römermann; Dylan Craven; et al. (Global Ecology and Biogeography, 2024)
Aim Understanding the mechanisms promoting resilience in plant communities is crucial in times of increasing disturbance and global environmental change. Here, we present the first meta‐analysis evaluating the relationship between functional diversity and resilience of plant communities. Specifically, we tested whether the resilience of plant communities is positively correlated with interspecific trait variation (following the niche complementarity hypothesis) and the dominance of acquisitive and small‐size species (following the mass ratio hypothesis), and for the context‐dependent effects of ecological and methodological differences across studies. Location Global. Time Period 2004–2021. Major Taxa Studied Vascular plants. Methods We compiled a dataset of 69 independent sites from 26 studies that have quantified resilience. For each site, we calculated functional diversity indices based on the floristic composition and functional traits of the plant community (obtained from the TRY database) which we correlated with resilience of biomass and floristic composition. After transforming correlation coefficients to Fisher's Z ‐scores, we conducted a hierarchical meta‐analysis, using a multilevel random‐effects model that accounted for the non‐independence of multiple effect sizes and the effects of ecological and methodological moderators. Results In general, we found no positive functional diversity–resilience relationships of grand mean effect sizes. In contrast to our expectations, we encountered a negative relationship between resilience and trait variety, especially in woody ecosystems, whereas there was a positive relationship between resilience and the dominance of acquisitive species in herbaceous ecosystems. Finally, the functional diversity–resilience relationships were strongly affected by both ecological (biome and disturbance properties) and methodological (temporal scale, study design and resilience metric) characteristics. Main Conclusions We rejected our hypothesis of a general positive functional diversity–resilience relationship. In addition to strong context dependency, we propose that idiosyncratic effects of single resident species present in the communities before the disturbances and biological legacies could play major roles in the resilience of terrestrial plant communities.

Influence of 8-weeks of supervised static stretching or resistance training of pectoral major muscles on maximal strength, muscle thickness and range of motion - Tim Wohlann; Konstantin Warneke; Vincent Kalder; David G. Behm; Tobias Schmidt; Stephan Schiemann (European Journal of Applied Physiology, 2024)
Objectives Current research suggests static stretch-induced maximal strength increases and muscle hypertrophy with potential to substitute resistance-training routines. However, most studies investigated the plantar flexors. This study explored the effects of a static stretching program on maximal strength, hypertrophy and flexibility of the pectoralis major and compared the effects with those of traditional resistance training. Methods Eighty-one (81) active participants were allocated to either a static stretching, strength-training or control group. Pectoralis stretching was applied 15 min/day, 4 days per week for 8 weeks, while resistance training trained 3 days per week, 5 × 12 repetitions. Results There was an increase in all parameters (strength: p < 0.001, ƞ 2 = 0.313, muscle thickness: p < 0.001, ƞ 2 = 0.157–0.264, flexibility: p < 0.001, ƞ 2 = 0.316) and a time*group interaction (strength: p = 0.001, ƞ 2 = 0.154, muscle thickness: p = 0.008–0.001, ƞ 2 = 0.117–0.173, flexibility: p < 0.001, ƞ 2 = 0.267). Post-hoc testing showed no difference between both intervention groups regarding maximal strength and muscle thickness ( p = 0.905–0.983, d = 0.036–0.087), while flexibility increased in the stretching group ( p = 0.001, d = 0.789). Conclusion Stretching showed increases in maximal strength and hypertrophy, which were comparable with commonly used resistance training. Based on current literature, the influence of mechanical tension as the underlying mechanism is discussed. Furthermore, as equipment and comparatively long stretching durations are requested to induce meaningful strength increases in recreationally active participants, practical application seems limited to special circumstances.

Mechanistic Modeling of In Vitro Biopharmaceutic Data for a Weak Acid Drug: A Pathway Towards Deriving Fundamental Parameters for Physiologically Based Biopharmaceutic Modeling - Venkata Krishna Kowthavarapu; Nitin Bharat Charbe; Churni Gupta; Tatiana Iakovleva; Cordula Stillhart; Neil John Parrott; Stephan Schmidt; Rodrigo Cristofoletti (The AAPS Journal, 2024)

Imidazolium salts are effective for the control of Culex quinquefasciatus larvae and demonstrate low impact on non-target organisms - Harry Luiz Pilz-Júnior; Stephanie Jansen; Carolina Maicá Silva; Juliana Fank Gomes; Débora Rech Volz; Alessandra Bittencourt de Lemos; Wellington Junior da Silva; Tarcisio Freitas Milagres; Josiane Somariva Prophiro; Jonas Schmidt-Chanasit; Ana Luiza Ziulkoski; Eliane Dallegrave; et al. (Journal of Pest Science, 2024)

Failure to predict amikacin elimination in critically ill patients with cancer based on the estimated glomerular filtration rate: applying PBPK approach in a therapeutic drug monitoring study - João Paulo Telles; Mariana Suelotto Diegues; Karen Cristina Migotto; Olivia de Souza Borges; Rodrigo Reghini; Brenda Vianna Gavazza; Leonardo Pinto; Pedro Caruso; Ivan Leonardo França e Silva; Stephan Schmidt; Fernanda de Lima Moreira (European Journal of Clinical Pharmacology, 2023)

Standards of NGS Data Sharing and Analysis in Ataxias: Recommendations by the NGS Working Group of the Ataxia Global Initiative - Danique Beijer; Brent L. Fogel; Sergi Beltran; Matt C. Danzi; Andrea H. Németh; Stephan Züchner; Matthis Synofzik; Astrid Adarmes; Saud Alhusaini; Mahmoud Reza Ashrafi; Luis Bataller; Enrico Bertini; et al. (The Cerebellum, 2023)
The Ataxia Global Initiative (AGI) is a worldwide multi-stakeholder research platform to systematically enhance trial-readiness in degenerative ataxias. The next-generation sequencing (NGS) working group of the AGI aims to improve methods, platforms, and international standards for ataxia NGS analysis and data sharing, ultimately allowing to increase the number of genetically ataxia patients amenable for natural history and treatment trials. Despite extensive implementation of NGS for ataxia patients in clinical and research settings, the diagnostic gap remains sizeable, as approximately 50% of patients with hereditary ataxia remain genetically undiagnosed. One current shortcoming is the fragmentation of patients and NGS datasets on different analysis platforms and databases around the world. The AGI NGS working group in collaboration with the AGI associated research platforms—CAGC, GENESIS, and RD-Connect GPAP—provides clinicians and scientists access to user-friendly and adaptable interfaces to analyze genome-scale patient data. These platforms also foster collaboration within the ataxia community. These efforts and tools have led to the diagnosis of > 500 ataxia patients and the discovery of > 30 novel ataxia genes. Here, the AGI NGS working group presents their consensus recommendations for NGS data sharing initiatives in the ataxia field, focusing on harmonized NGS variant analysis and standardized clinical and metadata collection, combined with collaborative data and analysis tool sharing across platforms.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Soil–plant interactions modulated water availability of Swiss forests during the 2015 and 2018 droughts - Katrin Meusburger; Volodymyr Trotsiuk; Paul Schmidt‐Walter; Andri Baltensweiler; Philipp Brun; Fabian Bernhard; Mana Gharun; Raphael Habel; Frank Hagedorn; Roger Köchli; Achilleas Psomas; Heike Puhlmann; et al. (Global Change Biology, 2022)
Central Europe has been experiencing unprecedented droughts during the last decades, stressing the decrease in tree water availability. However, the assessment of physiological drought stress is challenging, and feedback between soil and vegetation is often omitted because of scarce belowground data. Here we aimed to model Swiss forests' water availability during the 2015 and 2018 droughts by implementing the mechanistic soil‐vegetation‐atmosphere‐transport (SVAT) model LWF‐Brook90 taking advantage of regionalized depth‐resolved soil information. We calibrated the model against soil matric potential data measured from 2014 to 2018 at 44 sites along a Swiss climatic and edaphic drought gradient. Swiss forest soils' storage capacity of plant‐available water ranged from 53 mm to 341 mm, with a median of 137 ± 42 mm down to the mean potential rooting depth of 1.2 m. Topsoil was the primary water source. However, trees switched to deeper soil water sources during drought. This effect was less pronounced for coniferous trees with a shallower rooting system than for deciduous trees, which resulted in a higher reduction of actual transpiration (transpiration deficit) in coniferous trees. Across Switzerland, forest trees reduced the transpiration by 23% (compared to potential transpiration) in 2015 and 2018, maintaining annual actual transpiration comparable to other years. Together with lower evaporative fluxes, the Swiss forests did not amplify the blue water deficit. The 2018 drought, characterized by a higher and more persistent transpiration deficit than in 2015, triggered widespread early wilting across Swiss forests that was better predicted by the SVAT‐derived mean soil matric potential in the rooting zone than by climatic predictors. Such feedback‐driven quantification of ecosystem water fluxes in the soil–plant‐atmosphere continuum will be crucial to predicting physiological drought stress under future climate extremes.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

The β-Secretase Substrate Seizure 6–Like Protein (SEZ6L) Controls Motor Functions in Mice - Emma Ong-Pålsson; Jasenka Rudan Njavro; Yvette Wilson; Martina Pigoni; Andree Schmidt; Stephan A. Müller; Michael Meyer; Jana Hartmann; Marc Aurel Busche; Jenny M. Gunnersen; Kathryn M. Munro; Stefan F. Lichtenthaler (Molecular Neurobiology, 2022)
The membrane protein seizure 6–like (SEZ6L) is a neuronal substrate of the Alzheimer’s disease protease BACE1, and little is known about its physiological function in the nervous system. Here, we show that SEZ6L constitutive knockout mice display motor phenotypes in adulthood, including changes in gait and decreased motor coordination. Additionally, SEZ6L knockout mice displayed increased anxiety-like behaviour, although spatial learning and memory in the Morris water maze were normal. Analysis of the gross anatomy and proteome of the adult SEZ6L knockout cerebellum did not reveal any major differences compared to wild type, indicating that lack of SEZ6L in other regions of the nervous system may contribute to the phenotypes observed. In summary, our study establishes physiological functions for SEZ6L in regulating motor coordination and curbing anxiety-related behaviour, indicating that aberrant SEZ6L function in the human nervous system may contribute to movement disorders and neuropsychiatric diseases.

Neuroinflammation in Primary Cultures of the Rat Spinal Dorsal Horn Is Attenuated in the Presence of Adipose Tissue–Derived Medicinal Signalling Cells (AdMSCs) in a Co-cultivation Model - Stephan Leisengang; Laura B. Heilen; Michele C. Klymiuk; Franz Nürnberger; Daniela Ott; Kathrin Wolf-Hofmann; Rüdiger Gerstberger; Christoph Rummel; Martin J. Schmidt; Stefan Arnhold; Joachim Roth (Molecular Neurobiology, 2022)
Neuroinflammation within the superficial dorsal horn (SDH) of the spinal cord induces inflammatory pain with symptoms of hyperalgesia and allodynia. Glial activation and production of inflammatory mediators (e.g. cytokines) is associated with modulation of nociceptive signalling. In this context, medicinal signalling cells, e.g. obtained from adipose tissue (AdMSCs), gained attention due to their capacity to modulate the inflammatory response in several diseases, e.g. spinal cord injury. We applied the recently established mixed neuroglial primary cell culture of the rat SDH to investigate effects of AdMSCs on the inflammatory response of SDH cells. Following establishment of a co-cultivation system, we performed specific bioassays for tumour necrosis factor alpha (TNFα) and interleukin (IL)-6, RT-qPCR and immunocytochemistry to detect changes in cytokine production and glial activation upon inflammatory stimulation with lipopolysaccharide (LPS). LPS-induced expression and release of pro-inflammatory cytokines (TNFα, IL-6) by SDH cells was significantly attenuated in the presence of AdMSCs. Further evidence for anti-inflammatory capacities of AdMSCs derived from a blunted LPS-induced TNFα/IL-10 expression ratio and suppressed nuclear translocation of the inflammatory transcription factor nuclear factor kappa B (NFκB) in SDH microglial cells. Expression of IL-10, transforming growth factor beta (TGF-β) and TNFα-stimulated gene-6 (TSG-6) was detected in AdMSCs, which are putative candidates for anti-inflammatory capacities of these cells. We present a novel co-cultivation system of AdMSCs with neuroglial primary cultures of the SDH to investigate immunomodulatory effects of AdMSCs at a cellular level.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Biallelic variants in YRDC cause a developmental disorder with progeroid features - Julia Schmidt; Jonas Goergens; Tatiana Pochechueva; Annika Kotter; Niko Schwenzer; Maren Sitte; Gesa Werner; Janine Altmüller; Holger Thiele; Peter Nürnberg; Jörg Isensee; Yun Li; et al. (Human Genetics, 2021)
The highly conserved YrdC domain-containing protein (YRDC) interacts with the well-described KEOPS complex, regulating specific tRNA modifications to ensure accurate protein synthesis. Previous studies have linked the KEOPS complex to a role in promoting telomere maintenance and controlling genome integrity. Here, we report on a newborn with a severe neonatal progeroid phenotype including generalized loss of subcutaneous fat, microcephaly, growth retardation, wrinkled skin, renal failure, and premature death at the age of 12 days. By trio whole-exome sequencing, we identified a novel homozygous missense mutation, c.662T > C, in YRDC affecting an evolutionary highly conserved amino acid (p.Ile221Thr). Functional characterization of patient-derived dermal fibroblasts revealed that this mutation impairs YRDC function and consequently results in reduced t 6 A modifications of tRNAs. Furthermore, we established and performed a novel and highly sensitive 3-D Q-FISH analysis based on single-telomere detection to investigate the impact of YRDC on telomere maintenance. This analysis revealed significant telomere shortening in YRDC-mutant cells. Moreover, single-cell RNA sequencing analysis of YRDC-mutant fibroblasts revealed significant transcriptome-wide changes in gene expression, specifically enriched for genes associated with processes involved in DNA repair. We next examined the DNA damage response of patient’s dermal fibroblasts and detected an increased susceptibility to genotoxic agents and a global DNA double-strand break repair defect. Thus, our data suggest that YRDC may affect the maintenance of genomic stability. Together, our findings indicate that biallelic variants in YRDC result in a developmental disorder with progeroid features and might be linked to increased genomic instability and telomere shortening.

sPlotOpen – An environmentally balanced, open‐access, global dataset of vegetation plots - Francesco Maria Sabatini; Jonathan Lenoir; Tarek Hattab; Elise Aimee Arnst; Milan Chytrý; Jürgen Dengler; Patrice De Ruffray; Stephan M. Hennekens; Ute Jandt; Florian Jansen; Borja Jiménez‐Alfaro; Jens Kattge; et al. (Global Ecology and Biogeography, 2021)
Motivation Assessing biodiversity status and trends in plant communities is critical for understanding, quantifying and predicting the effects of global change on ecosystems. Vegetation plots record the occurrence or abundance of all plant species co‐occurring within delimited local areas. This allows species absences to be inferred, information seldom provided by existing global plant datasets. Although many vegetation plots have been recorded, most are not available to the global research community. A recent initiative, called ‘sPlot’, compiled the first global vegetation plot database, and continues to grow and curate it. The sPlot database, however, is extremely unbalanced spatially and environmentally, and is not open‐access. Here, we address both these issues by (a) resampling the vegetation plots using several environmental variables as sampling strata and (b) securing permission from data holders of 105 local‐to‐regional datasets to openly release data. We thus present sPlotOpen, the largest open‐access dataset of vegetation plots ever released. sPlotOpen can be used to explore global diversity at the plant community level, as ground truth data in remote sensing applications, or as a baseline for biodiversity monitoring. Main types of variable contained Vegetation plots ( n = 95,104) recording cover or abundance of naturally co‐occurring vascular plant species within delimited areas. sPlotOpen contains three partially overlapping resampled datasets ( c . 50,000 plots each), to be used as replicates in global analyses. Besides geographical location, date, plot size, biome, elevation, slope, aspect, vegetation type, naturalness, coverage of various vegetation layers, and source dataset, plot‐level data also include community‐weighted means and variances of 18 plant functional traits from the TRY Plant Trait Database. Spatial location and grain Global, 0.01–40,000 m². Time period and grain 1888–2015, recording dates. Major taxa and level of measurement 42,677 vascular plant taxa, plot‐level records. Software format Three main matrices (.csv), relationally linked.

Spatial population genomics of a recent mosquito invasion - Thomas L. Schmidt; Tom Swan; Jessica Chung; Stephan Karl; Samuel Demok; Qiong Yang; Matt A Field; Mutizwa Odwell Muzari; Gerhard Ehlers; Mathew Brugh; Rodney Bellwood; Peter Horne; et al. (Molecular Ecology, 2021)
Population genomic approaches can characterize dispersal across a single generation through to many generations in the past, bridging the gap between individual movement and intergenerational gene flow. These approaches are particularly useful when investigating dispersal in recently altered systems, where they provide a way of inferring long‐distance dispersal between newly established populations and their interactions with existing populations. Human‐mediated biological invasions represent such altered systems which can be investigated with appropriate study designs and analyses. Here we apply temporally restricted sampling and a range of population genomic approaches to investigate dispersal in a 2004 invasion of Aedes albopictus (the Asian tiger mosquito) in the Torres Strait Islands (TSI) of Australia. We sampled mosquitoes from 13 TSI villages simultaneously and genotyped 373 mosquitoes at genome‐wide single nucleotide polymorphisms (SNPs): 331 from the TSI, 36 from Papua New Guinea (PNG) and four incursive mosquitoes detected in uninvaded regions. Within villages, spatial genetic structure varied substantially but overall displayed isolation by distance and a neighbourhood size of 232–577. Close kin dyads revealed recent movement between islands 31–203 km apart, and deep learning inferences showed incursive Ae. albopictus had travelled to uninvaded regions from both adjacent and nonadjacent islands. Private alleles and a co‐ancestry matrix indicated direct gene flow from PNG into nearby islands. Outlier analyses also detected four linked alleles introgressed from PNG, with the alleles surrounding 12 resistance‐associated cytochrome P450 genes. By treating dispersal as both an intergenerational process and a set of discrete events, we describe a highly interconnected invasive system.

Tribute to Professor Hartmut Derendorf—1953 to 2020: The gentle giant of quantitative clinical pharmacology - Stephan Schmidt (Journal of Pharmacokinetics and Pharmacodynamics, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Towards regulatory endorsement of drug development tools to promote the application of model-informed drug development in Duchenne muscular dystrophy - Daniela J. Conrado; Jane Larkindale; Alexander Berg; Micki Hill; Jackson Burton; Keith R. Abrams; Richard T. Abresch; Abby Bronson; Douglass Chapman; Michael Crowther; Tina Duong; Heather Gordish-Dressman; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2019)

Assessment of mixture toxicity of (tri)azoles and their hepatotoxic effects in vitro by means of omics technologies - Bettina Seeger; Almut Mentz; Constanze Knebel; Flavia Schmidt; Hanna Bednarz; Karsten Niehaus; Stephan Albaum; Jörn Kalinowski; Thomas Noll; Pablo Steinberg; Philip Marx-Stoelting; Tanja Heise (Archives of Toxicology, 2019)

LCA of key technologies for future electricity supply—68th LCA forum, Swiss Federal Institute of Technology, Zurich, 16 April, 2018 - Rolf Frischknecht; Christian Bauer; Christof Bucher; Linda Ager-Wick Ellingsen; Lukas Gutzwiller; Britta Heimbach; René Itten; Xun Liao; Evangelos Panos; Stephan Pfister; Tobias Schmidt; Valentin Stahel; et al. (The International Journal of Life Cycle Assessment, 2018)

EXIOBASE 3: Developing a Time Series of Detailed Environmentally Extended Multi‐Regional Input‐Output Tables - Konstantin Stadler; Richard Wood; Tatyana Bulavskaya; Carl‐Johan Södersten; Moana Simas; Sarah Schmidt; Arkaitz Usubiaga; José Acosta‐Fernández; Jeroen Kuenen; Martin Bruckner; Stefan Giljum; Stephan Lutter; et al. (Journal of Industrial Ecology, 2018)
Summary Environmentally extended multiregional input‐output (EE MRIO) tables have emerged as a key framework to provide a comprehensive description of the global economy and analyze its effects on the environment. Of the available EE MRIO databases, EXIOBASE stands out as a database compatible with the System of Environmental‐Economic Accounting (SEEA) with a high sectorial detail matched with multiple social and environmental satellite accounts. In this paper, we present the latest developments realized with EXIOBASE 3—a time series of EE MRIO tables ranging from 1995 to 2011 for 44 countries (28 EU member plus 16 major economies) and five rest of the world regions. EXIOBASE 3 builds upon the previous versions of EXIOBASE by using rectangular supply‐use tables (SUTs) in a 163 industry by 200 products classification as the main building blocks. In order to capture structural changes, economic developments, as reported by national statistical agencies, were imposed on the available, disaggregated SUTs from EXIOBASE 2. These initial estimates were further refined by incorporating detailed data on energy, agricultural production, resource extraction, and bilateral trade. EXIOBASE 3 inherits the high level of environmental stressor detail from its precursor, with further improvement in the level of detail for resource extraction. To account for the expansion of the European Union (EU), EXIOBASE 3 was developed with the full EU28 country set (including the new member state Croatia). EXIOBASE 3 provides a unique tool for analyzing the dynamics of environmental pressures of economic activities over time.

Plant growth promotion of Miscanthus × giganteus by endophytic bacteria and fungi on non-polluted and polluted soils - Christoph Stephan Schmidt; Libor Mrnka; Tomáš Frantík; Petra Lovecká; Miroslav Vosátka (World Journal of Microbiology and Biotechnology, 2018)

Development of an Enantioselective and Biomarker-Informed Translational Population Pharmacokinetic/Pharmacodynamic Model for Etodolac - Carolina de Miranda Silva; Adriana Rocha; Eduardo Tozatto; Lucienir Maria da Silva; Eduardo Antônio Donadi; Teresa Dalla Costa; Vera Lucia Lanchote; Stephan Schmidt; Jürgen B. Bulitta (The AAPS Journal, 2017)

Government and biodiversity governance in Post-Soviet Azerbaijan: an institutional perspective - Sebastian Schmidt; Stephan Busse; Elshan Nuriyev (Environment, Development and Sustainability, 2017)

Immunohistochemical analysis of the anterior nervous system of the free-living nematode Plectus spp. (Nematoda, Plectidae) - Stephan Henne; Andy Sombke; Andreas Schmidt-Rhaesa (Zoomorphology, 2017)

The effects of different aerobic exercise intensities on serum serotonin concentrations and their association with Stroop task performance: a randomized controlled trial - Philipp Zimmer; Christian Stritt; Wilhelm Bloch; Frank-Peter Schmidt; Sven Thorsten Hübner; Stephan Binnebößel; Alexander Schenk; Max Oberste (European Journal of Applied Physiology, 2016)

Population Pharmacokinetic Modeling of Etoposide Free Concentrations in Solid Tumor - Maiara Cássia Pigatto; Bibiana Verlindo de Araujo; Bruna Gaelzer Silva Torres; Stephan Schmidt; Paolo Magni; Teresa Dalla Costa (Pharmaceutical Research, 2016)

New encounters in Arctic waters: a comparison of metabolism and performance of polar cod (Boreogadus saida) and Atlantic cod (Gadus morhua) under ocean acidification and warming - Kristina Lore Kunz; Stephan Frickenhaus; Silvia Hardenberg; Torild Johansen; Elettra Leo; Hans-Otto Pörtner; Matthias Schmidt; Heidrun Sigrid Windisch; Rainer Knust; Felix Christopher Mark (Polar Biology, 2016)

Cytokine kinetics of Zika virus-infected patients from acute to reconvalescent phase - Dennis Tappe; José Vicente Pérez-Girón; Lorenzo Zammarchi; Jürgen Rissland; Davis F. Ferreira; Thomas Jaenisch; Sergio Gómez-Medina; Stephan Günther; Alessandro Bartoloni; César Muñoz-Fontela; Jonas Schmidt-Chanasit (Medical Microbiology and Immunology, 2016)

High genetic structuring of Tula hantavirus - Sabrina Schmidt; Moritz Saxenhofer; Stephan Drewes; Mathias Schlegel; Konrad M. Wanka; Raphael Frank; Sven Klimpel; Felix von Blanckenhagen; Denny Maaz; Christiane Herden; Jona Freise; Ronny Wolf; et al. (Archives of Virology, 2016)

Aufbau eines bodenhydrologischen Messnetzes in der sibirischen Kulundasteppe - Eckart Stephan; Ralph Meißner; Holger Rupp; Manfred Frühauf; Gerd Schmidt; Patrick Illiger; Andrej A. Bondarovitsch; Dmitri N. Balykin; Vsevolod V. Scherbinin; Alexander W. Puzanov (WASSERWIRTSCHAFT, 2014)

Application of a mechanism-based disease systems model for osteoporosis to clinical data - Teun M. Post; Stephan Schmidt; Lambertus A. Peletier; Rik de Greef; Thomas Kerbusch; Meindert Danhof (Journal of Pharmacokinetics and Pharmacodynamics, 2013)

Stenotrophomonas rhizophila DSM14405T promotes plant growth probably by altering fungal communities in the rhizosphere - Christoph Stephan Schmidt; Mohamadali Alavi; Massimiliano Cardinale; Henry Müller; Gabriele Berg (Biology and Fertility of Soils, 2012)

Coping with time scales in disease systems analysis: application to bone remodeling - Stephan Schmidt; Teun M. Post; Lambertus A. Peletier; Massoud A. Boroujerdi; Meindert Danhof (Journal of Pharmacokinetics and Pharmacodynamics, 2011)

PI3 kinase-dependent stimulation of platelet migration by stromal cell-derived factor 1 (SDF-1) - Bjoern F. Kraemer; Oliver Borst; Eva-Maria Gehring; Tanja Schoenberger; Benjamin Urban; Elena Ninci; Peter Seizer; Christine Schmidt; Boris Bigalke; Miriam Koch; Ivo Martinovic; Karin Daub; et al. (Journal of Molecular Medicine, 2010)

Transcranial direct current stimulation affects visual perception measured by threshold perimetry - Antje Kraft; Jasper Roehmel; Manuel C. Olma; Sein Schmidt; Kerstin Irlbacher; Stephan A. Brandt (Experimental Brain Research, 2010)

Insights into the molecular basis of the microaerophily of three Campylobacterales: a comparative study - Nadeem O. Kaakoush; Claudia Baar; Joanna MacKichan; Peer Schmidt; Edward M. Fox; Stephan C. Schuster; George L. Mendz (Antonie van Leeuwenhoek, 2009)

Non-Gaussian curvature distribution of actin-propelled biomimetic colloid trajectories - Stephan Schmidt; Jasper van der Gucht; P. Maarten Biesheuvel; Richard Weinkamer; Emmanuèle Helfer; Andreas Fery (European Biophysics Journal, 2008)

Magnetic resonance imaging of the lumbar spine and blood volume in professional cyclists - Stefan Vogt; Carsten Altehoefer; Dirk Bueltermann; Torben Pottgiesser; Stephan Prettin; Andreas Schmid; Kai Roecker; Walter Schmidt; Katja Heinicke; Lothar Heinrich (European Journal of Applied Physiology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Influence of soil type and pH on the colonisation of sugar beet seedlings by antagonistic Pseudomonas and Bacillus strains, and on their control of Pythium damping-off - Christoph Stephan Schmidt; Francesco Agostini; Ana-maria Simon; Jennifer Whyte; John Townend; Carlo Leifert; Ken Killham; Chris Mullins (European Journal of Plant Pathology, 2004)

Life cycle assessment of lightweight and end-of-life scenarios for generic compact class passenger vehicles - Wulf-Peter Schmidt; Elisabeth Dahlqvist; Matthias Finkbeiner; Stephan Krinke; Silvia Lazzari; Dirk Oschmann; Sophie Pichon; Christian Thiel (The International Journal of Life Cycle Assessment, 2004)

Data collection format for life cycle assessment of the german association of the automotive industry (VDA) - Matthias Finkbeiner; Stephan Krinke; Dirk Oschmann; Thomas Saeglitz; Siegfried Schaper; Wulf-Peter Schmidt; Ralf Schnell (The International Journal of Life Cycle Assessment, 2003)